Identifikasi Dampak Gangguan Harmonisa dan Ketidak Seimbangan Magnitude Tegangan Serta Sudut Phasa Pada Performa Motor Induksi - harjono, Purwo (Faculty of Engineering, Universitas Tanjungpura, 2014)
Abstract– The quality of supply system is found to be very effective in deteriorating the performance of three phase induction motors, a class of electrical machines which is widely used in industrial power systems. This paper presents an attempt to identify the impacts of harmonics and unbalance on induction motor performance. The presence of voltage magnitude and/or phase angle unbalance in the supply system is considered as well as harmonics distortion. Computer simulations of a VFD fed induction motor under different quality conditions of supply system are implemented using Powersim (PSIM). Six scenarios of harmonics contained supply system are tested, i.e. scenario 1 : balanced voltage magnitude, balanced phase angle and balanced transformer; scenario 2 : balanced voltage magnitude, balanced phase angle and unbalanced transformer; scenario 3 : unbalanced voltage magnitude, balanced phase angle and balanced transformer; scenario 4 : unbalanced voltage magnitude, balanced phase angle and unbalanced transformer; scenario 5 : balanced voltage magnitude, unbalanced phase angle and balanced transformer, and scenario 6 : balanced voltage magnitude, unbalanced phase angle and unbalanced transformer. The test results indicate that the quality of supply system has significant impacts on the speed and mechanical torque of three phase induction motor operating with harmonics contained and unbalanced supply system. Keywords– harmonics, unbalance, voltage magnitude, phase angle, induction motor.